2022
DOI: 10.1101/2022.11.23.517678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An FcRn-targeted mucosal vaccine against SARS-CoV-2 infection and transmission

Abstract: SARS-CoV-2 and its variants cause COVID-19, which is primarily transmitted through droplets and airborne aerosols. To prevent viral infection and reduce viral spread, vaccine strategies must elicit protective immunity in the airways. FcRn transfers IgG across epithelial barriers; we explore FcRn-mediated respiratory delivery of SARS-CoV-2 spike (S). A monomeric IgG Fc was fused to a stabilized S protein; the resulting S-Fc bound to S-specific antibodies (Ab) and FcRn. A significant increase in Ab responses was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…In addition to these infectious vaccines, the Fc fusion strategy has been used in several studies to develop vaccine against SARS-CoV-2. In this regard, some investigators fused Fc portion to spike protein [40] and some others used RBD-Fc fusion protein [12,32,[41][42][43][44]. The Fc fusion protein were able to induce potent immune responses that are biased towards Th1 with high levels of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these infectious vaccines, the Fc fusion strategy has been used in several studies to develop vaccine against SARS-CoV-2. In this regard, some investigators fused Fc portion to spike protein [40] and some others used RBD-Fc fusion protein [12,32,[41][42][43][44]. The Fc fusion protein were able to induce potent immune responses that are biased towards Th1 with high levels of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that intramuscular vaccines are not effective at hampering viral replication and shedding in the upper respiratory tract, so while symptoms are milder, the virus can still be transmitted [82]. The appeal for IN vaccinations lies in the fact that they have shown promise to induce sterilizing immunity against mucosal pathogens [83], which could prevent virus infection, replication, shedding, and disease development, while also limiting viral transmission. Most recently, researchers have developed an IN immunization that is being tested in animal models and which has demonstrated promising results by significantly reducing viral replication in the nasal mucosa, lungs, and brains in mice and significantly reducing viral airborne transmission in hamsters [84].…”
Section: Vaccines and The Role Of Boostersmentioning
confidence: 99%
“…1c). Immunization strategies such as nonconventional adjuvants [77,84], alternative antigen vectors [79,80,[85][86][87], or intranasal administration [78,[88][89][90] have all shown promise in providing superior immune protection of the nasal passages, though careful differential analysis of olfactory and respiratory tissues has not been performed. The exact signals that dictate protective OM plasma cell homing and protection remain to be precisely identified, but the discovery of the BOB has important implications for the design of vaccines that aim to protect the olfactory mucosa.…”
Section: Adaptive Immune Responsementioning
confidence: 99%